Labour Market Performance Effects of Discrimination and Loss of Skill. Extended version - Birthe Larsen; Gisela Waisman (Copenhagen Business School (CBS), Department of Economics, 2015)
We examine the impact of discrimination on labour market performance when workers are subject to a risk of losing skills during an unemployment experience. Within a search and matching framework, we show that both natives and immigrants are affected by discrimination. Discrimination in one sector has positive spill-overs, inducing employment to increase in the other sector and the effect on labour market performance therefore depends on whether discrimination is present in only one sector or in both sectors. Discrimination may induce workers to train more or less than natives after having lost their skills, dependent upon which sector there is discrimination. Net output tends to the be most negatively affected by discrimination among high-skilled workers
hdl:10398/9157
Keywords: J15; J31; J61; J64; J71; 330; discrimination; unemployment; search and matching; wages